MEMPROMOSIKAN AMSAL DALAM KATEKESE KELUARGA - Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2018)
The Book of Proverbs is a book in both the Tanakh (Judaism), and the Old Testament (Christianity). The book contains some of the most important teaching and instructions in each of their respective Religions. Most scholars believe that Solomon was the writer of at least part of the book Other authors are mentioned as well, but these references are missing in the Greek Septuagint. The Septuagint sees King Solomon as the author of the whole Book of Proverbs This paper will punctuate the option for Christian family to apply Proverbs in family catechesis. Christian family must be helped in according to preach the value of faith. Teaching with Proverbs that influenced by any parents may be the effective evangelization.